Node cookbook : practical solutions to server-side JavaScript problems - Clements, David Mark; Buus, Matthias; Collina, Matteo; Elger, Peter (Packt Publishing, 2017)
Over 60 high-quality recipes covering debugging, security, performance, microservices, web frameworks, databases, deployment and more; rewritten for Node 4, 6, and 8. About This Book Actionable recipes across the full spectrum of Node.js development Cutting edge techniques and tools for measuring and improving performance Best practices for creating readily-scalable production systems Who This Book Is For If you have good knowledge of JavaScript and want to build fast, efficient, scalable client-server solutions, then this book is for you. Some experience with Node.js is assumed to get the most out of this book. If working from a beginner level Node Cookbook 2nd Edition is recommended as a primer for Node Cookbook 3rd Edition. What You Will Learn Debug Node.js programs Write and publish your own Node.js modules Detailed coverage of Node.js core API's Use web frameworks such as Express, Hapi and Koa for accelerated web application development Apply Node.js streams for low-footprint data processing Fast-track performance knowledge and optimization abilities Persistence strategies, including database integrations with MongoDB, MySQL/MariaDB, Postgres, Redis, and LevelDB Apply critical, essential security concepts Use Node with best-of-breed deployment technologies: Docker, Kubernetes and AWS In Detail Today's web demands efficient real-time applications and scalability. Asynchronous event-driven programming is ideal for this, and this is where Node.js comes in. Server-side JavaScript has been here since the 90s, but Node got it right. With Node for tooling and server-side logic, and a browser-based client-side UI, everything is JavaScript. This leads to rapid, fluid development cycles. The full-stack, single language experience means less context-switching between languages for developers, architects and whole teams. This book shows you how to build fast, efficient, and scalable client-server solutions using the latest versions of Node. The book begins with debugging tips and tricks of the trade, and how to write your own modules. Then you'll learn the fundamentals of streams in Node.js, discover I/O control, and how to implement the different web protocols. You'll find recipes for integrating databases such as MongoDB, MySQL/MariaDB, Postgres, Redis, and LevelDB. We also cover the options for building web application with Express, Hapi and Koa. You will then learn about security essentials in Node.js and advanced optimization tools and technique ...